Análise das prevalências de doenças detectadas pelo programa nacional de triagem neonatal no município de Araraquara no ano de 2009 - Vespoli, S. [UNESP]; Marques, M. [UNESP]; Marane, S. S G [UNESP]; Santos, V. F. [UNESP]; Chin, Chung Man [UNESP]; Santos, Jean Leandro dos [UNESP] (My University, 2011)
The National Neonatal Screening Program (NNSP) set up in all Brazil, aims, through planned phases of local implementation, to detect diseases such as phenylketonuria, congenital hypothyroidism, hemoglobinopathies and cystic fibrosis. The aim of this study was to assess, through a cross-sectional observational study, the prevalence of the diseases detected by the NNSP in the city of Araraquara, in records issued by the São Paulo APAE laboratory in the period between April and December 2009.The results show that Araraquara had a prevalence of phenylketonuria and congenital hypothyroidism 0.06% above the national averages of 0.01% and 0.03% respectively. With respect to hemoglobinopathies, the prevalence of sickle cell trait was 2.15% below the national average of 2.6%. The prevalence of Hb C in the city was 0.57%, similar to national values reported in the literature. Confirmed Hb Bart's had a prevalence of 0.13% in Araraquara, below the average of 0.38% for the surrounding region. The neonatal screening by heel-prick test and counseling for caregivers are important factors in reducing morbidity related to the evolution of these diseases.

O Programa Nacional de Triagem Neonatal (PNTN) implantado no Brasil tem como objetivo, considerando cada fase de execução local, detectar doenças como fenilcetonúria, hipotereoidismo congênito, hemoglobinopatias e fibrose cística. O objetivo deste trabalho foi analisar, através de um estudo transversal e observacional, a prevalência das doenças detectadas pelo PNTN no município de Araraquara emitidas pela APAE de São Paulo no período compreendido entre abril e dezembro de 2009. Os resultados mostram que o município apresentou, no ano de 2009, prevalência de fenilcetonúria e hipotireoidismo congênito de 0,06% acima da média nacional, que é de 0,01% e 0,03%, respectivamente. Com relação às hemoglobinopatias, encontrou-se prevalência do traço para anemia falciforme de 2,15% abaixo da média nacional, que é de 2,6%. A prevalência do traço C no município foi de 0,57%, semelhante a valores nacionais disponíveis na literatura. FA BART’S confirmado apresentou valor de 0,13% abaixo da média de 0,38% da região do município de Araraquara. A realização do teste do pezinho e o aconselhamento aos cuidadores são fatores importantes para redução de morbidades relacionadas à evolução dessas doenças. Palavras-chave: Triagem neonatal. Teste do pezinho. Anemia falciforme. Fenilcetonúria. Fibrose cística. Hipotireoidismo congênito.
Prevalence analysis of diseases detected by the National Neonatal Screening Program in Araraquara city (Brazil) in the year 2009
Keywords: Congenital hypothyroidism; Cystic fibrosis; Heel-prick test; Neonatal screening; Phenylketonuria; Sickle cell anemia; Brazil; congenital hypothyroidism; cystic fibrosis; hemoglobin C disease; hemoglobinopathy; human; newborn; newborn screening; phenylketonuria; prevalence; sickle cell trait